Metode Pembuatan Sorgum Sosoh Rendah Tanin pada Pembuatan Nasi Sorgum (Sorghum Bicolor L) Instan - Wiwit Amrinola; Sri Widowati; Purwiyatno Hariyadi (Bina Nusantara University, 2015)
Sorghum is one of the non-rice commodities which have a relatively high content of nutrients, especially protein and carbohydrate. However, the nutritional value is to be down and relatively low due to the relatively high tannin content as an anti-nutrient. Fairly high tannin content in sorghum is also causing sorghumhas unpleasant taste and slightly bitter or